Synthesis of tautomeric forms of 5-(2-Hydroxyphenyl)-4-substituted-3H-1,2, 4-triazole-3-thione - Cansiz, Ahmet; Çetin, Ahmet; Kutulay, Pelin; Koparir, Metin (Chemical Publishing Co., 2009)
In this study, salicylic acid hydrazide 1 was converted into 1,4-substituted thiosemicarbazides (2a-f). The 1,4-substituted thiosemicarbazides were then converted into 5-(2-hydroxy phenyl)-4-substituted- 3H-1,2,4-triazole-3-thione (3a-f). In addition, the aminomethylation compounds of 5-(2-hydroxy phenyl)-4-substituted-3H-1,2,4-triazole-3-thione (4a-f) were synthesized by the Mannich reaction of 3a-f and then {[5-(2-hydroxy phenyl)-4-methyl-4H-1,2,4-triazol-3-yl]thio}acetic acid (5a-f) were prepared by 3a-f. The structures of all the synthesized compounds were confirmed by elemental analyses, X-ray, FT-IR, 1H NMR and 13C NMR spectra. Their thiolthione tautomeric equilibrium is described.
Keywords: 1,2,4-Triazole; Thiol/thione tautomeric forms